The Time-Course of Changes in Muscle Mass, Architecture and Power During 6 Weeks of Plyometric Training - Monti, Elena; Franchi, Martino V.; Badiali, Francesca; Quinlan, Jonathan I.; Longo, Stefano; Narici, Marco V. (Frontiers in Physiology, 2020)
Purpose: To investigate the time-course of changes in knee-extensors muscle mass, architecture and function in response to plyometric training (PLT). Methods: 8 healthy males (173.6 ± 4.7 cm, 69.7 ± 13.5 kg, 25.3 ± 4.6 years) underwent 6 weeks of bilateral PLT. Knee extensor maximum voluntary torque (MVT) and leg extensors power (LEP), quadriceps femoris (QF) volume (VOL), cross-sectional area from the 20% to the 60% of femur length and CSAmean, together with vastus lateralis (VL) architecture (fascicle length, Lf, and pennation angle, PA) were assessed after 2, 4 and 6 wks of PLT. Results: All results are presented as changes versus baseline. MVT increased by 17.8% (wk 2, p<0.001) and 22.2% (wk 4, p<0.01), respectively, and declined to 13.3% (p<0.05) at wk 6 of PLT. LEP increased by 18.2% (wk 4, p<0.05) and 19.7% (wk 6, p<0.05). An increase in Lf was detected already at wk 2 (2.2%, p<0.05), with further increase at 4 and 6 wk of PLT (4% and 4.4%, respectively, p<0.01). PA increased by 5.8% (p<0.05) at wk 6. QF VOL increased by 4.7% (wk 4, p<0.05) and 5.8% (wk 6, p<0.01); VL VOL increased by 5.2%, (p<0.05), 8.2%, (p<0.01) and 9.6% (p<0.05) at wk 2, 4 and 6 respectively. Significant positive correlations were found between CSAmean and LEP (R2=0.46, p<0.001) and between QF VOL and LEP (R2=0.44, p<0.024). Conclusions: PLT induces rapid increases in muscle volume, fascicle length, pennation angle, torque and power in healthy younger adults. Notably, changes in VL volume and fascicle length were detectable already after 2 weeks, followed by increases in knee extensors volume and power from week 4 of PLT.